Irrigation agriculture affects organic matter decomposition in semi-arid terrestrial and aquatic ecosystems - Arroita, Maite; Causape, Jesus; Comin, Francisco A.; Diez, Joserra; Jose Jimenez, Juan; Lacarta, Juan; Lorente, Carmen; Merchan, Daniel; Muniz, Selene; Navarro, Enrique; Val, Jonatan; Elosegi, Arturo (JOURNAL OF HAZARDOUS MATERIALS, 2013)
Many dryland areas are being converted into intensively managed irrigation crops, what can disrupt the hydrological regime, degrade soil and water quality, enhance siltation, erosion and bank instability, and affect biological communities. Still, the impacts of irrigation schemes on the functioning of terrestrial and aquatic ecosystems are poorly understood. Here we assess the effects of irrigation agriculture on breakdown of coarse organic matter in soil and water. We measured breakdown rates of alder and holm oak leaves, and of poplar sticks in terrestrial and aquatic sites following a gradient of increasing irrigation agriculture in a semi-arid Mediterranean basin transformed into irrigation agriculture in 50% of its surface. Spatial patterns of stick breakdown paralleled those of leaf breakdown. In soil, stick breakdown rates were extremely low in non-irrigated sites (0.0001-0.0003 day(-1)), and increased with the intensity of agriculture (0.0018-0.0044 day(-1)). In water, stick breakdown rates ranged from 0.0005 to 0.001 day(-1), and increased with the area of the basin subject to irrigation agriculture. Results showed that irrigation agriculture affects functioning of both terrestrial and aquatic ecosystems, accelerating decomposition of organic matter, especially in soil. These changes can have important consequences for global carbon budgets. (C) 2013 Elsevier B.V. All rights reserved.
The following values have no corresponding Zotero field: pub-location: PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS publisher: ELSEVIER SCIENCE BV
Keywords: breakdown; ecosystem functioning; Irrigation agriculture; Soil; Stream

Effects of Leaf Litter Species on Macroinvertebrate Colonization during Decomposition in a Portuguese Stream - Abelho, Manuela (International Review of Hydrobiology, 2008)
This study evaluated if there are differences in leaf breakdown and invertebrate colonization among tree species differing in quality (toughness), and which factors could influence these differences. Common alder leaves decomposed significantly faster then either sweet chestnut or Spanish oak (k values of –0.0332, –0.0108, and –0.0112, respectively) during the first 2 months. Shredder abundance was highest when leaf mass remaining was 50%, and the samples clustered in mixed groups of sampling dates and leaf species, suggesting that stage of decomposition was an important factor influencing shredder colonization. During the first two months of decomposition, the physicochemical characteristics of leaf litter and the interaction between leaf toughness and the occurrence of frequent spates seemed to be the main factors affecting leaf breakdown rates in the stream. (© 2008 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)
Keywords: breakdown; colonisation; leaves; river; shredders

Effects of Leaf Litter Species on Macroinvertebrate Colonization during Decomposition in a Portuguese Stream - Abelho, Manuela (International Review of Hydrobiology, 2008)
This study evaluated if there are differences in leaf breakdown and invertebrate colonization among tree species differing in quality (toughness), and which factors could influence these differences. Common alder leaves decomposed significantly faster then either sweet chestnut or Spanish oak (k values of –0.0332, –0.0108, and –0.0112, respectively) during the first 2 months. Shredder abundance was highest when leaf mass remaining was 50%, and the samples clustered in mixed groups of sampling dates and leaf species, suggesting that stage of decomposition was an important factor influencing shredder colonization. During the first two months of decomposition, the physicochemical characteristics of leaf litter and the interaction between leaf toughness and the occurrence of frequent spates seemed to be the main factors affecting leaf breakdown rates in the stream. (© 2008 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)
The following values have no corresponding Zotero field: publisher: WILEY-VCH Verlag
Keywords: breakdown; colonisation; leaves; river; shredders